2019
DOI: 10.1002/jid.3410
|View full text |Cite
|
Sign up to set email alerts
|

Does the Geographic Expansion of Microfinance Branches Affect Profitability? Panel Data Evidence from Sub‐Saharan Africa

Abstract: Notwithstanding the recent banking innovations, like mobile money services, microfinance institutions still rely on brick-and-mortar branches to provide financial services to the poor in the sub-Saharan Africa (SSA) region. Moreover, the number of microfinance branches has continued to increase remarkably since the early 2000s. In light of that, we study the influence of geographic expansion of the branches network on the profitability of 343 microfinance institutions operating in 36 countries of SSA over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…If these operational challenges can be overcome, it will be easier for MFIs to expand their services to reach lower levels of society. In addition, Chikalipah [46] explain the relationship between increased profitability and expansion of the microfinance branch. Widyaningrum, Bhat, and Lee [47] study on microfinance market opportunities in Indonesia showed that MFIs have the potential to have around 50 million household customers so that MFIs can take advantage of the large segmentation in the microfinance sector.…”
Section: Analysis Of Swot (Strength Weakness Opportunity and Threat)mentioning
confidence: 99%
“…If these operational challenges can be overcome, it will be easier for MFIs to expand their services to reach lower levels of society. In addition, Chikalipah [46] explain the relationship between increased profitability and expansion of the microfinance branch. Widyaningrum, Bhat, and Lee [47] study on microfinance market opportunities in Indonesia showed that MFIs have the potential to have around 50 million household customers so that MFIs can take advantage of the large segmentation in the microfinance sector.…”
Section: Analysis Of Swot (Strength Weakness Opportunity and Threat)mentioning
confidence: 99%
“…34. See Caserta, Monteleone and Reito (2018), Chikalipah (2019) and Lam et al (2019) for recent evidence. Abraham (1984), Fafchamps (1992) and Matin et al (2002) show that the poor use savings and credit as substitutes.…”
Section: Savingsmentioning
confidence: 99%